2020
DOI: 10.1039/d0nj00960a
|View full text |Cite
|
Sign up to set email alerts
|

Improved Ti species distribution and hierarchical pores in TS-1: towards regeneration of TS-1 deactivated due to alkali corrosion

Abstract: TS-1 deactivated in industrial cyclohexanone ammoximation can be effectively regenerated by hydrothermal treatment with TPABr and ethanolamine solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…Doelle et al have reported similar results of the diffusion process of hydrocarbon molecules on the ZSM-5 zeolite. 59 After supporting HPMo or HPMo-H 2 O 2 on Nano-TS-1, the conclusion is consistent with the result of the parent. For larger BT and DBT, the number of saturated organic sulfur molecules slightly increases.…”
Section: Characterization Of Samplessupporting
confidence: 77%
See 1 more Smart Citation
“…Doelle et al have reported similar results of the diffusion process of hydrocarbon molecules on the ZSM-5 zeolite. 59 After supporting HPMo or HPMo-H 2 O 2 on Nano-TS-1, the conclusion is consistent with the result of the parent. For larger BT and DBT, the number of saturated organic sulfur molecules slightly increases.…”
Section: Characterization Of Samplessupporting
confidence: 77%
“…The aggregation of nanoparticles that emerge in the SEM images of HPMo-Nano-TS-1 and HPMo-H 2 O 2 -Nano-TS-1 is consistent with the FT-IR and XRD results. 58,59 The TEM images of Nano-TS-1, HPMo-Nano-TS-1, and HPMo-H 2 O 2 -Nano-TS-1 catalysts are shown in Fig. 7.…”
Section: Characterization Of Samplesmentioning
confidence: 99%
“…The formation of mesopores may be attributed to the polyethylene glycol in the precipitated silica. The increase in the surface area and mesopores in zeolite can improve the mass transfer performance of reaction species in the channel. …”
Section: Resultsmentioning
confidence: 99%
“…Another approach is to post-treatment the final TS-1 with organic alkalis. 106 , 207 , 246 , 247 , 248 , 249 , 250 , 251 Alkalis dissolve the zeolite and remove the Si matrix from the framework, resulting in the formation of micro- and mesoporous composite layers. Recently, TPAOH has been applied as a hot spot etchant to create hierarchical TS-1 zeolites by desilication.…”
Section: Ts-1 Catalyst Design For Efficient Catalytic Performancementioning
confidence: 99%